THE RELATIONSHIP BETWEEN PREECLAMPSIA AND PARITY IN MATERNAL BIRTH IN RSUD MUHAMMAD SANI KARIMUN - Bratasena Bratasena; Junita Henriette (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background : In Indonesia, eclampsia in addition to bleeding and infection is still the main cause of maternal mortality and a high cause of perinatal mortality. Therefore, early diagnosis of preeclampsia, which is a preliminary level of eclampsia, and its handling need to be implemented immediately to reduce maternal and child mortality (Prawiroharjo, 2012). Method : The research design used was case control. Population is the whole object of research. The population in this study were all women who gave birth at Muhammad Sani Karimun Hospital, namely 218 people with the number of preeclampsia incidents of 30 people. The number of cases to be used is 2 (two) times the number of cases, namely 60 people. The analysis used was the Ods Ratio (OR), which is a measure of the association of exposure (risk factors) with the incidence of disease in the risk group (exposed to risk factors) compared to the incidence of disease in the group that is not at risk (not exposed to risk factors). Result : The results of the study, the value of the Prevalence Odds Ratio (POR) = 6,875 with a value of 95% Confidence Interval (CI) = 3,318-12,410. Congclusions : The conclusion of this research is that respondents with high parity are 6.8 times more likely to experience preeclampsia than respondents with little parity.